Heyzine Website Development Based on Guidance in Giving Service Guidance Information at MAN 1 Makassar City - Nur Faisah Atirah Faisal; Ratna Wulandari; Sandi Pratama (Information Technology Education Journal, 2025)
Development Heyzine website based about guidance in giving service information at MAN 1 Makassar City. Research This aim For know use development Heyzine website based on guidance in giving service information. Developing the heyzine website for know effectiveness in giving service information in guidance and counseling. Research Methods and Development (R&D) is used in study This with model ADDIE procedural research This held at MAN 1 Makassar City during One month start from April to May 2025. Techniques used that is random sampling technique . Research result show that heyzine website development based on guidance in giving service information use emodul in giving service information on the eye lesson Guidance and Counseling (BK), has innovation latest in giving its services, namely digital book media that is packaged in e- module which is accompanied by fun games and various type material in accordance need from participant students who are in the Madrasah Aliyah (MA) realm or School Senior High School (SMA). Criteria validity Innovation latest from e- module This with percentage of 91.3% in eligibility unique use Study while play.